Queer theory and social change - Kirsch, Max H., 1953- (Routledge, 2000)
"The emergence of queer theory represents a huge leap in our understanding of lesbian and gay peoples. It embodies a context for treating these people as worthy of consideration in their own rights and not as an appendage to general cultural theory. Max Kirsch argues that the current development of this area is in danger of repeating past mistakes in the construction of analyses, and ultimately, social movements. In this way, the book presents an alternative to the current fascination with the abstract categories of identity, culture and difference, and emphasizes the need for a discussion of the importance of communities and globalization on queer movements."--Jacket